2021
DOI: 10.1002/ange.202015713
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Production of HCOOH from CO2 Electroreduction via Bi/CeOx

Abstract: Formic acid (HCOOH) is one of the most promising chemical fuels that can be produced through CO 2 electroreduction. However, most of the catalysts for CO 2 electroreduction to HCOOH in aqueous solution often suffer from low current density and limited production rate. Herein, we provide a bismuth/cerium oxide (Bi/CeO x) catalyst, which exhibits not only high current density (149 mA cm À2), but also unprecedented production rate (2600 mmol h À1 cm À2) with high Faradaic efficiency (FE, 92 %) for HCOOH generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Fundamental advances in electrocatalysts, 3 electrolytes 4 and electrochemical cell designs, 5 have propelled AP technologies to a point where scale-up of electrolysis is beginning to occur for generating simple C 1 products such as carbon monoxide, 6,7 syngas, 8,9 and formate/formic acid [10][11][12][13][14][15] with relatively high selectivity and reaction rates. Distinct classes of CO 2 RR electrocatalysts have been found that discriminate between the formate and carbon monoxide pathways, 1,16,25 thereby allowing C 1 product selectivity and suppressing self-poisoning by CO.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental advances in electrocatalysts, 3 electrolytes 4 and electrochemical cell designs, 5 have propelled AP technologies to a point where scale-up of electrolysis is beginning to occur for generating simple C 1 products such as carbon monoxide, 6,7 syngas, 8,9 and formate/formic acid [10][11][12][13][14][15] with relatively high selectivity and reaction rates. Distinct classes of CO 2 RR electrocatalysts have been found that discriminate between the formate and carbon monoxide pathways, 1,16,25 thereby allowing C 1 product selectivity and suppressing self-poisoning by CO.…”
Section: Introductionmentioning
confidence: 99%
“…With half‐filled p ‐orbitals, the elements of the VA group are of special interest [16, 17] . While various oxidation states are known for N ( 2s 2 2p 3 ), the first element of the VA group, [18–20] the reported oxidation states for Bi ( 6s 2 6p 3 ), the last element of the VA group, are mainly 0 and +3 [21–23] . Modulation of the p ‐orbital energies for Bi has been scarcely investigated, also making the identification of the active phase of Bi during catalysis quite difficult [24] …”
Section: Introductionmentioning
confidence: 99%
“…[16,17] While various oxidation states are known for N (2s 2 2p 3 ), the first element of the VA group, [18][19][20] the reported oxidation states for Bi (6s 2 6p 3 ), the last element of the VA group, are mainly 0 and + 3. [21][22][23] Modulation of the p-orbital energies for Bi has been scarcely investigated, also making the identification of the active phase of Bi during catalysis quite difficult. [24] With ultra-low proton and electron affinities, the N 2 molecule is known to be chemically inert under a wide range of conditions and, accordingly, difficult to be activated by most transition metal (d-orbital) catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of CeO X on the electronic structure has not been debated in detail. Recent studies revealed that the introduction of CeO 2 can prevent Cu 2+ from being reduced to strengthen the adsorption of CO* on catalysts, thus promoting the efficient production of CH 4 . However, although the role of CeO 2 in CO 2 reduction reaction has been investigated in numerous studies, the correlation between the adsorption of the key intermediate with the electronic structure and dynamic structural evolution of ceria-incorporated sulfide materials has not been systemically explored.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that the introduction of CeO 2 can prevent Cu 2+ from being reduced to strengthen the adsorption of CO* on catalysts, thus promoting the efficient production of CH 4 . 22 However, although the role of CeO incorporated sulfide materials has not been systemically explored.…”
Section: Introductionmentioning
confidence: 99%